Monoclonal antibodies to cerebellar pinceau terminals obtained after immunization with brain mRNA-injected Xenopus oocytes. - Tigyi, G (1990)
A method was developed to produce monoclonal antibodies to brain cell antigens by using Xenopus oocytes as immunological vectors. The method consists in injecting Xenopus oocytes with rat brain mRNA to express foreign proteins and using the oocytes for immunization. Immunizations were preceded by immunotolerization of mice to antigens of native oocyte membranes. With this approach we generated a set of monoclonal antibodies that are specific markers for the cerebellar "pinceau"--a unique complex synapse formed between basket cell terminals and the initial segment of the Purkinje cell axon. Our findings reveal an immunoreactivity highly localized at the pinceau and its late expression beginning at postnatal day 19 during cerebellar development.